Function of the Neuropilin Family as Essential Pleiotropic Cell Surface Receptors - Parker, Matthew W. (2012)
The neuropilin (Nrp) family are essential multifunctional vertebrate cell surface receptors. Nrps were initially characterized as receptors for class III Semaphorin (Sema3) family members, functioning in axon guidance. Nrps have also been shown to be critical for Vascular Endothelial Growth Factor (VEGF) dependent angiogenesis. Intriguingly, recent data show that Nrp function in these seemingly divergent pathways is critically determined by ligand-mediated cross-talk, which underlies Nrp function in both physiological and pathological processes. In addition to functioning in these two pathways, Nrps have been shown to specifically function in a number of other fundamental signaling pathways as well. Multiple general mechanisms have been found to directly contribute to the pleiotropic function of Nrp. Here we review critical general features of Nrps function as essential receptors integrating multiple molecular cues into diverse cellular signaling.